2011
DOI: 10.4209/aaqr.2010.12.0113
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of PM2.5 and PM2.5-10 at Inland and Offshore Sites over Southeastern Coastal Region of Taiwan Strait

Abstract: This study investigates the effects of sea-land breezes (SLBs) and northeastern monsoon (NEM) on the physicochemical properties of particulate matter (PM) in the atmosphere over southeastern coastal region of Taiwan Strait. The intensive PM sampling protocol was consecutively conducted for forty-eight hours. During the sampling periods, PM 2.5 and PM 2.5-10 were simultaneously measured with dichotomous samplers at four sites (two inland and two at offshore sites) and PM 10 was measured with beta-ray monitors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 44 publications
3
20
0
Order By: Relevance
“…Aerosol size and size distribution are important aspects of aerosol physical properties, and the particle number concentration of fine particles should get more attention than the mass concentration (Tsai et al, 2011;Gómez-Moreno, 2011;Ny and Lee, 2011;Du et al, 2012). Previous studies of particle size distribution in Shanghai have shown that the average particle number concentrations (10-100 nm) are 2-3 times higher than those reported in the urban areas of North America and Europe (Kulmala et al, 2004;Gao et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
“…Aerosol size and size distribution are important aspects of aerosol physical properties, and the particle number concentration of fine particles should get more attention than the mass concentration (Tsai et al, 2011;Gómez-Moreno, 2011;Ny and Lee, 2011;Du et al, 2012). Previous studies of particle size distribution in Shanghai have shown that the average particle number concentrations (10-100 nm) are 2-3 times higher than those reported in the urban areas of North America and Europe (Kulmala et al, 2004;Gao et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
“…However, these reports did not discuss the metallic characteristics under the different transport routes. Although several investigations have examined the characteristics and sources of PM 2.5 , PM 2.5-10 , and PM 10 in Kaohsiung over the past decade (Lin, 2002;Chen et al, 2003;Tsai and Chen, 2006;Hsu et al, 2008;Tsai et al, 2010;Tsai et al, 2011). These previous studies were conducted only over short sampling periods (several months); longer campaigns (e.g., one year) to determine the chemical characteristics of metallic elements in PM 2.5 and PM 2.5-10 are still rare.…”
Section: Introductionmentioning
confidence: 99%
“…The aerodynamic diameters of PM 2.5 are from ~0 to 2.5 µm, while those of PM 10 ranges from ~0 to 10 µm (Chow et al, 2015). Both PM 2.5 and PM 10 are made up of other subclasses of pollutants with the major ones being water soluble ions such as SO 4 2-, NH 4 + , and NO 3 -and metal elements as minor constituents (Tsai et al, 2011;Xu et al, 2012;Chang et al, 2013) as well as carbonaceous species such as the organic carbon (OC) and elemental carbon (EC) Ho et al, 2006) and volatile organics (Cheruiyot et al, 2015). Particulate matter is emitted into the atmosphere from primary sources which can be either natural or anthropogenic (Kong et al, 2014;Alghamdi et al, 2015) and also from secondary formation in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%